PENGARUH KEBERLANJUTAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN DENGAN KARAKTERISTIK CEO SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018 - 2021) - Rahmawati, Isna; Juliarto, Agung (Diponegoro Journal of Accounting, 2024)
The study aims to examine the effect of corporate sustainability on firm performance with CEO characteristics as the moderating variable. Corporate sustainability is the independent variable and firm performance is the dependent variable. CEO characteristics as a moderating variable are proxied by the variable education level, tenure, and gender.The sample of this research is non financial companies listed on the Indonesia Stock Exchange in 2018-2021 with a total of 50 companies. The sample selection method used a purposive sampling method in the form of criteria and requirements that have been determined by the researcher. Regression analysis and absolute difference value tests were used in this research.The result of the study shows that corporate sustainability have a positive effect on firm performance. The CEO’s education level strengthen the influence of corporate sustainability on firm performance. However, this research finds that a longer CEO tenure weakens the influence of corporate sustainability on firm performance. Likewise in terms of gender, female CEOs can not strengthen the influence of corporate sustainability on firm performance.